The legend of Kevin - Reeve, Philip; McIntyre, Sarah (Oxford : Oxford University Press, 2018)
"Max is a young boy living in an ordinary tower block. He longs for adventure in his life - then one day - DOOF! - a flying pony called Kevin crashes into his flat, blown in by a magical storm! The storm causes a huge flood and soon Max's town submerged by water. Luckily for the town, Max has a flying pony to come to the rescue, and luckily for Kevin, he has a new best friend and a constant supply of his favourite thing - biscuits. Together Max and Kevin will embark on many wild adventures together."--Publisher's description.
3-6.
English.
Keywords: Human-animal relationships -- Juvenile fiction; Ponies -- Juvenile fiction; Human-animal relationships; Ponies; Children's stories; Humorous fiction